Global spatially explicit crop water consumption shows an overall increase of 9% for 46 agricultural crops from 2010 to 2020 - Chukalla, A. D.; Mekonnen, M. M.; Gunathilake, Dahami; Wolkeba, F. T.; Gunasekara, Bhawani; Vanham, Davy (Nature Portfolio, 2025)
Agricultural crop production is the largest water user worldwide. Here we compute the blue and green water consumption (WC) of global crop production at 5 arcminutes (~10 km at the equator) for the year 2020, differentiating between 46 crops, using the most recent Spatial Production Allocation Model 2020 crop data. Total crop WC amounts to 6,668 km3, or 6,817 km3 including the flooding phase of paddy rice, of which green WC amounts to 5,588 km3 and blue WC to 1,080 km3 (increasing to 1,228 km3 with paddy flooding). Over a period of 20 years, five major crops increased in total WC by 23–82%. For 2010–2020, global total crop WC increased by 9% from 6,270 km3 (with paddy flooding). Alongside observed increases in cropland area, higher crop WC puts additional pressure on limited water resources.